Diskursus Cadar dalam Memaknai Pandemi Covid-19; Suatu Kajian Syariat dan Fungsi Medis - Mustafa, Adriana; Mujahidah, Nurul (Mazahibuna: Jurnal Perbandingan Mazhab, 2020)
Since the outbreak of disease in Indonesia is Corona virus, the Indonesian government issued several policies and provisions on the procedure of living a life during the pandemic. One of the most common things to do is the implementation of a clean and healthy lifestyle as well as using masks. The emergence of policies to always use masks raises thoughts or opinions that can lead to the friction of understanding for the society, especially Muslims. The opinion is the assumption of some people who believe that the use of veil as an obligation for women of Muslimah more obedient to the recommendation of the Government is not appealed by the command of God to use the veil. Until finally the virus appears and requires that each person use a mask judged as a blow for those who do not run the order of use of the veil. However, such thinking does not have to arise and propagate in people's lives, because the use of the veil itself has a different opinion, both among modern scholars and classical scholars. Therefore, both obliging and not requiring the veil is expected to continue to carry out the recommendations and policies issued by the Government, especially the use of masks during pandemic as it is today.